Clinical Outcome of the Patients Undergoing Monopolar Transurethral Resection of Prostate for Symptomatic Benign Enlargement of Prostate - KC, Sudeep Raj; giri, Saroj; Upadhyay, Hari Prasad; Timilsina, Bhushan; Pradhan, Sulav; Kumar Kushwaha, Dipesh; Mahaseth, Naveen (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Benign prostatic hyperplasia (BPH) is the most common benign tumor in men. Transurethral resection of prostate (TURP) is a commonly performed urologic operation for the treatment of symptoms associated with BPH. TURP reduces lower urinary tract symptoms and also reduces the International Prostate Symptom Score (IPSS) in 94.7% cases of clinical BPH and improves quality of life in patients with BPH. The objective of this research is to analyse the clinical outcomes of patients undergoing monopolar transurethral resection of the prostate for symptomatic benign enlargement of the prostate in our center. Methods A Retrospective cross-sectional study was conducted at the Department of Urology COMS Teaching Hospital among the patients who underwent monopolar TURP from 2019 to 2022. Patient records were collected from hospital operation books and OPD records, and further inquiry was made via phone calls. Based on the available data we analyzed the Patient's Age, Size of the prostate, Pre and post-operative IPSS, QOL score and Qmax, Operative time and complications. Results A total of 167 patients underwent M – TURP during the study period. The mean age of patients who underwent TURP was 70.49 years. The average size of the prostate was 63.08 grams. The mean operating time was 60.09 minutes with a mean hospital stay of 5.99 days. The preoperative IPSS was 28.92, QOL was 4.72 and QMax was 9.27 and Post-operative mean IPSS, QOL score and Qmax was 5.38, 0.98 and 19.7 respectively with a p-value of less than 0.05. Conclusions Surgery is the mainstay of treatment in BPH if conservative and medical therapy fails. There are several endourological treatments available for BPH today, but monopolar TURP is still widely used in developing countries and is a standard treatment for BPH-related LUTS. Outcomes are comparable to other treatment modalities if done timely and meticulously.